Effects of changes in temperature on treatment performance and energy recovery at mainstream anaerobic ceramic membrane bioreactor for food waste recycling wastewater treatment. (May 2018) - Cho, Kyungjin; Jeong, Yeongmi; Seo, Kyu Won; Lee, Seockheon; Smith, Adam L.; Shin, Seung Gu; Cho, Si-Kyung; Park, Chanhyuk
Graphical abstract: Highlights: Low-temperature anaerobic ceramic membrane bioreactor was evaluated. AnCMBR for treating a dilute FRW and domestic wastewater mixture. AnCMBR was successfully applied at ambient temperature for co-managing DWW and FRW. Microbial community structure was shifted by the temperature changes. Methanogenic activity was inhibited at 15 °C in AnCMBR treatment. Abstract: An anaerobic ceramic membrane bioreactor (AnCMBR) has been attracted as an alternative technology to co-manage various organic substrates. This AnCMBR study investigated process performance and microbial community structure at decreasing temperatures to evaluate the potential of AnCMBR treatment for co-managing domestic wastewater (DWW) and food waste-recycling wastewater (FRW). As a result, the water flux (≥6.9 LMH) and organic removal efficiency (≥98.0%) were maintained above 25 °C. The trend of methane production in the AnCMBR was similar except for at 15 °C. At 15 °C, the archaeal community structure did not shifted, whereas the bacterial community structure was changed. Various major archaeal species were identified as the mesophilic methanogens which unable to grow at 15 °C. Our results suggest that the AnCMBR can be applied to co-manage DWW and FRW above 20 °C. Future improvements including psychrophilic methanogen inoculation and process optimization would make co-manage DWW and FRW at lower temperature climates.